AN ANALYSIS OF LIBERTARIAN RADICAL FEMINISM ON RIEâS CHARACTER IN JOYCE LEBRA THE SCENT OF SAKE (2009) - Rullyanti, Merry; Sari, Sinta Purnama (LITERARY CRITICISM, 2015)
Literature has close relationship with humanâs life. It could not separate with society as the writer is member of society. It represents the life and life itself is social fact. Feminism theory has purpose to know the nature of inequality and focus on power, gender politics and sexuality. While generally feminist theory also concern to analyze womenâs right, interest and issues. The themes usually explored in feminism such as oppression, patriarchy, discrimination, etc. One of that is libertarian radical feminism that related to patriarchy is characterised by power and propose detrimental for men to exhibit only masculine traits and women to exhibit only feminine traits. The aimed of this study are to know Rieâs life toward tradition with domination of man power and to find out libertarian radical feminism characteristics that possessed by Rie in the scent of sake novel. From the finding of the writer found about Rieâs life as the main character in The Scent of Sake novel, she occurs many oppression from patriarchy which domination of men and women become passive just take care to her husband, house and children. She must receive her parents decision to marring with man who didnât love her, she is sacrifice herself to get heir from that man consider to business family. Then she still survive with the act of her husband and the last she knows that her husband has been cheat to geishas and has babies whereas she canât has it too. Because of that, her libertarian radical feminism characteristics rise up. It also caused by her parents died and make her aware that she must take control in her family, she canât depend her life to her husband that waste much money to geisha. She changes become independent and androgynious women by her education. However, Sake business and the other business that her family become more successful in Rieâs leadership. She really has soul of successor in Sake business.Â Keywords : Libertarian radical feminism, The Scent of Sake novel